(3eaGgje aj GdejcGfjc Gdcej (B= s CONCEPTES OF QUANTUM MECGANICS - (3MSf, efGa YHOs ((3YeGf, GdGQOf (B: s (3OGQ GdKbGaI ddfTQ hGdJhRjY, s, 2003)
(3jJVef GdeaGgje GdGSGSjI dfXQjI Gdce ef NdGd SQO ehSY ddeHGOiA GdGSGSjI ddfXQjI s (3jJVef GdYOjO ef GdGeKdI GdeMdhdI hZjQ GdeMdhdI(B. s
(3jJVef GQLGYGJ HHdjhLQGajI(B.s
Keywords: (3ejcGfjc Gdce s